2019
DOI: 10.3390/ijerph17010160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-Week Functional Training Intervention on the Speed of Young Footballers

Abstract: The aim of the research was to verify the functional state of young football players using selected tests of the Functional Movement Screen (FMS) protocol, as well as the impact of the 12 weeks of functional training on the speed parameters. The research was conducted on 20 highly competitive young (U17) football players. Research project was conducted in two stages: in the first part of the study, the functional assessment was made by using the FMS test, then the measurement of the speed parameters was done w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 34 publications
2
54
0
Order By: Relevance
“…Three studies were not included in the meta-analysis for the following reasons: one was missing data regarding the total FMS™ scores and sports injury but included data regarding the strength and flexibility of the athletes ( Song et al., 2014 ), and two studies had single-group sample sizes fewer than 10 people and very low quality assessment scores (the PEDro quality scale score for physical therapy was only 4 points) ( Kim et al., 2014 ; Armstrong et al., 2019 ). Furthermore, some studies used a single-group pre-test design method to perform functional correction training for athletes and found that that they had a positive impact on the FMS™ scores, asymmetric events, and sports injuries ( Kiesel, Plisky & Butler, 2011 ; Lee, Zhang1 & Lee, 2015 ; Garbenyté-Apolinskiené et al., 2018 ; Tejani et al., 2019 ; Boucher et al., 2018 ; Baron et al., 2019 ; Huebner et al., 2019 ; Bayrakdar, Kılın & Boz, 2020 ). These studies did not meet the inclusion criteria and were excluded from this report.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were not included in the meta-analysis for the following reasons: one was missing data regarding the total FMS™ scores and sports injury but included data regarding the strength and flexibility of the athletes ( Song et al., 2014 ), and two studies had single-group sample sizes fewer than 10 people and very low quality assessment scores (the PEDro quality scale score for physical therapy was only 4 points) ( Kim et al., 2014 ; Armstrong et al., 2019 ). Furthermore, some studies used a single-group pre-test design method to perform functional correction training for athletes and found that that they had a positive impact on the FMS™ scores, asymmetric events, and sports injuries ( Kiesel, Plisky & Butler, 2011 ; Lee, Zhang1 & Lee, 2015 ; Garbenyté-Apolinskiené et al., 2018 ; Tejani et al., 2019 ; Boucher et al., 2018 ; Baron et al., 2019 ; Huebner et al., 2019 ; Bayrakdar, Kılın & Boz, 2020 ). These studies did not meet the inclusion criteria and were excluded from this report.…”
Section: Resultsmentioning
confidence: 99%
“…It is foot defects that can alter gait biomechanics, resulting in the ineffective performance of motor activities and a significant load on the athletes’ locomotor system [ 2 ]. As one of the contact sports, soccer can lead to injuries, especially in the foot and ankle, amounting to 20% of all injuries [ 12 , 13 ]. According to Bastos et al and Baron et al, soccer players who play in defensive positions, with frequent contact with the opponent, those who run at full speed with changes in directions and those who perform rapid accelerations at their position on the pitch are particularly vulnerable to musculoskeletal injuries [ 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the contact sports, soccer can lead to injuries, especially in the foot and ankle, amounting to 20% of all injuries [ 12 , 13 ]. According to Bastos et al and Baron et al, soccer players who play in defensive positions, with frequent contact with the opponent, those who run at full speed with changes in directions and those who perform rapid accelerations at their position on the pitch are particularly vulnerable to musculoskeletal injuries [ 5 , 13 ]. Improved performance, optimal preparation of players for performing sprints and changes of direction and reduced risk of injury can be achieved with properly designed warm-up routines before training and games [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were not included in the meta-analysis for the following reasons: one was missing data regarding the total FMS™ scores and sports injury but included data regarding the strength and flexibility of the athletes (Song et al, 2014), and two studies had single-group sample sizes fewer than 10 people and very low quality assessment scores (the PEDro quality scale score for physical therapy was only 4 points) (Kim et al, 2014;Armstrong et al, 2019). Furthermore, some studies used a single-group pre-test design method to perform functional correction training for athletes and found that that they had a positive impact on the FMS™ scores, asymmetric events, and sports injuries (Kiesel, et al, 2011;Jim et al,, 2015;Toma et al,2017;Ali et al,2019;Brende et al, PeerJ reviewing PDF | (2020:10:53313:2:1:NEW 17 Feb 2021) Manuscript to be reviewed 2018; Baron J et al, 2019;Huebner et al,2019;Bayrakdar et al, 2020. These studies did not meet the inclusion criteria and were excluded from this report.…”
Section: Study Characteristicsmentioning
confidence: 99%